\(Ps^-\) and \(H^+_2\) Ions under Spatial Confinement - Chandra, R.; Saha, Jayanta K.; Bhattacharyya, S.; Mukherjee, T. K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
The ground state energy eigenvalues of the spatially confined symmetric three-body exotic ions \(Ps^-\) and \(H^+_2\) have been determined under the framework of Rayleigh-Ritz variational method. The spatial confinement is simulated by considering an impenetrable spherical box of varying radius around the ion. The electron-electron correlation in \(Ps^-\)  and the protonproton correlation in \(H_+^2\) are properly taken care of by expanding the trial wavefunction in explicitly correlated Hylleraas type basis set. The critical radius and the corresponding critical pressure, at which the respective ions destabilize are also reported.